2014
DOI: 10.1063/1.4893696
|View full text |Cite
|
Sign up to set email alerts
|

Graphene chemical vapor deposition at very low pressure: The impact of substrate surface self-diffusion in domain shape

Abstract: The initial stages of graphene chemical vapor deposition at very low pressures (<10−5 Torr) were investigated. The growth of large graphene domains (∼up to 100 μm) at very high rates (up to 3 μm2 s−1) has been achieved in a cold-wall reactor using a liquid carbon precursor. For high temperature growth (>900 °C), graphene grain shape and symmetry were found to depend on the underlying symmetry of the Cu crystal, whereas for lower temperatures (<900 °C), mostly rounded grains are observed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Since 2004, numerous studies have confirmed that graphene has excellent electrical, mechanical and thermal properties. A myriad of protocols have been subsequently developed for Graphene-based nanomaterials: biological and medical applications and toxicity the production of graphene from a variety of sources using techniques such as CVD [12,13] 'graphitization of silicon carbide (SiC) surfaces' [14,15], intercalation/ exfoliation methods [16] and other reductive chemistry reactions [17].…”
mentioning
confidence: 99%
“…Since 2004, numerous studies have confirmed that graphene has excellent electrical, mechanical and thermal properties. A myriad of protocols have been subsequently developed for Graphene-based nanomaterials: biological and medical applications and toxicity the production of graphene from a variety of sources using techniques such as CVD [12,13] 'graphitization of silicon carbide (SiC) surfaces' [14,15], intercalation/ exfoliation methods [16] and other reductive chemistry reactions [17].…”
mentioning
confidence: 99%